Analisis Pembuktian Untuk Pertanggungjawaban Hukum Penerima Endorsement dalam Judi Online - Visia Nurmalita Trully; Alip Rahman; Anom Sutrisno (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the evidence of the element of "distributing and/or making accessible" online gambling content by endorsement recipients based on Article 27 paragraph (2) of the Electronic Information and Transactions Law and analyze their criminal liability. This study uses a normative juridical method with a statutory and conceptual approach. The results of the study indicate that the evidence must be based on the fulfillment of the elements of the crime, the element of intent, and valid electronic evidence. The criminal liability of endorsement recipients is analyzed based on the provisions of the ITE Law, the regulation of gambling crimes in the Criminal Code, and the concept of participation (deelneming), so that perpetrators who are proven to play an active role in promoting online gambling can be punished according to the provisions of statutory regulations.